2018
DOI: 10.1111/1467-8268.12334
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Food Security in African Countries

Abstract: Over the past decade, the amount of migrant remittances received by developing countries has increased rapidly.Several studies have analysed the impacts on growth, investment, education, and health. However, the effect on food security has not received much attention. This paper contributes to the literature by exploring the linkage between food security and international remittances using panel data during the period of 1990-2013 in African countries. The study employs an econometric model to test the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 20 publications
3
39
0
1
Order By: Relevance
“…This is consistent with a broader neglect of the connections between international and internal migration and food security [26][27][28]. More recently, several studies have demonstrated that there is a positive macro-level relationship between food security and the volume of remittances received [29][30][31][32].…”
Section: Introductionsupporting
confidence: 73%
“…This is consistent with a broader neglect of the connections between international and internal migration and food security [26][27][28]. More recently, several studies have demonstrated that there is a positive macro-level relationship between food security and the volume of remittances received [29][30][31][32].…”
Section: Introductionsupporting
confidence: 73%
“…i.e., a situation in which “all people, at all times, are free from hunger” (WFP, 2012, p. 170). This multidimensional definition is hinged on four pillars, namely: availability or the adequacy of food supply; food accessibility or affordability; the stability of supply without shortages or seasonal fluctuations; and utilization (Applanaidu et al, 2014; Mabrouk & Mekni, 2018; Nsiah & Fayissa, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…La problématique des déterminants de l'insécurité alimentaire et de la variation des revenus a fait l'objet de plusieurs recherches dans la littérature (Conceição et al, 2011; Etana & Tolossa, 2017; Mabrouk & Mekni, 2018; Olabiyi, 2020). Ainsi, elle indique que les chocs dans le secteur sanitaire ont généralement un impact négatif et significatif sur les activités économiques, du moins à court terme (Woldemichael & Gurmu, 2018).…”
Section: Brève Revue De Littératureunclassified